2017
DOI: 10.3390/pharmaceutics9040045
|View full text |Cite
|
Sign up to set email alerts
|

Disposition, Metabolism and Histone Deacetylase and Acetyltransferase Inhibition Activity of Tetrahydrocurcumin and Other Curcuminoids

Abstract: Tetrahydrocurcumin (THC), curcumin and calebin-A are curcuminoids found in turmeric (Curcuma longa). Curcuminoids have been established to have a variety of pharmacological activities and are used as natural health supplements. The purpose of this study was to identify the metabolism, excretion, antioxidant, anti-inflammatory and anticancer properties of these curcuminoids and to determine disposition of THC in rats after oral administration. We developed a UHPLC–MS/MS assay for THC in rat serum and urine. THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…We could previously show in TNF-β-stimulated CRC cells that NF-κB is a major target for the natural substance resveratrol in suppressing CRC tumor cell malignity [12,13,36,63]. Interestingly, a recent study could show that Calebin A mediates its anti-tumorogenic properties by inhibiting P300/CBP-associated factor (PCAF), which serves as transcriptional co-activator for both p53 and NF-kB [32,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could previously show in TNF-β-stimulated CRC cells that NF-κB is a major target for the natural substance resveratrol in suppressing CRC tumor cell malignity [12,13,36,63]. Interestingly, a recent study could show that Calebin A mediates its anti-tumorogenic properties by inhibiting P300/CBP-associated factor (PCAF), which serves as transcriptional co-activator for both p53 and NF-kB [32,65].…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, this effect was also observed in chemoresistant cells, underlining the immense potential of Calebin A as a chemopreventive/chemosensitivity agent to improve and enhance standard therapeutic approaches. Recently, it was shown that Calebin A exhibits anti-oxidant activity and inhibits histone acetyltransferase (HAT) activity and further mediates its anti-cancer effects by inhibiting P300/CBP-associated factor (PCAF) [32]. A plethora of nutraceuticals have also been shown to prevent NF-κB activation by the inhibition of IKK activity, phosphorylation and degradation of IκBα, nuclear translocation or binding of p65-NF-κB to the DNA [5].…”
Section: Introductionmentioning
confidence: 99%
“…CBA has a Michael acceptor group (C=C double bond) similar to curcumin. A previous study has attributed the group to CBA's capacity to inhibit histone acetyltransferase (HAT), similar to curcumin [40].…”
Section: Effects Of Cba On Ultrastructural Changes In Melanocytesmentioning
confidence: 99%
“…For example, a recent study reported synthesis of liposomes of CBA which showed antiproliferative effects in human colorectal cancer and mouse neuroblastoma cells [44]. has attributed the group to CBA's capacity to inhibit histone acetyltransferase (HAT), similar to curcumin [40].…”
Section: Effects Of Cba On Ultrastructural Changes In Melanocytesmentioning
confidence: 99%
“…Cur and THC in plasma and lung homogenates of mice were analysed by ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC/Q-TOF-MS) as described previously with modification. 24 The details of sample preparation and liquid chromatography/mass spectrometry analysis are described in the Appendix S1. Linearity was acquired using calibration curves between the concentration (X) and peak area (Y).…”
Section: Analysis Of Cur and Thc Levels In Plasma And Lung Tissuesmentioning
confidence: 99%